Daily performance optimization of a grid-connected hybrid system composed of photovoltaic and pumped hydro storage (PV/PHS) - Makhdoomi, Sina; Askarzadeh, Alireza (Renewable energy, 2020)
This paper presents a new methodology for minimizing daily operation cost of a grid-connected hybrid energy system composed of photovoltaic (PV) and pumped hydro storage (PHS) and evaluates the impact of water level on the system operation cost. For this aim, daily operation cost is defined as objective function and the value of power purchased from the grid at each hour is considered as decision variable (here 24 decision variables). The value of objective function is minimized subject to balance equation and reservoir water level. Owing to complexity of this optimization problem, a new variant of crow search algorithm (CSA), named differential CSA (CSAdif), has been developed to optimally utilize the hybrid system. Simulated results show that optimal combination of the components leads to considerable reduction of daily operation cost. Moreover, search capability of the proposed approach is more promising than that of the other studied techniques. •Daily operation cost of grid-connected PV/PHS has been minimized by a new approach.•Differential CSA finds more promising and robust results than other approaches.•Optimal combination of components will considerably decrease daily operation cost.